Rome and environs : an archaeological guide - Coarelli, Filippo (The Joan Palevsky imprint in classical literature, 2007)
Organised by walking tours, this guide covers various ancient sites of the city. It includes the major monuments in a large area outside Rome, such as Ostia Antica, Palestrina, Tivoli, and more. It is intended for tourists, as well as students and scholars approaching the ancient history of this city